Dampak Pemasaran Melalui Media Sosial Pada Sikap Terhadap Merek : Studi Produk Kosmetik Pada Generasi Z Di Kota Makassar - Muhammad Ashdaq; Syamsu Alam; Valentino Aris; Nur Fitriayu Mandasari (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Marketing through social media has become a marketing strategy that is widely used by the cosmetic industry, especially with the number of consumers that continues to grow along with the number of generations. Generation z women are a potential market in this industry where they are newcomer consumers and have a relatively large number compared to other generations. The purpose of this study was to investigate the effect of implementing marketing strategies through social media on Gen Z attitudes toward cosmetic products in the city of Makassar. The research was conducted by distributing questionnaires to 288 sample respondents. The primary data collected was then processed using the linear regression method using SPSS 23 software. The results showed that marketing through social media had a positive and significant effect on positive attitudes toward cosmetic products. The results of this study imply that cosmetic companies targeting the female gen z market in Makassar City should pay attention to the right social media marketing strategy to get a positive attitude from their consumers.